SIGNIFIKANSI DAKWAH INKLUSIF NURCHOLISH MADJID BAGI MASYARAKAT INDONESIA - Zaprulkhan Zaprulkhan (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2016)
Articulation of religion in the public sphere of Indonesia is still much to be exclusive and puritan, unilateral in monopolizing the truth claims of religious truth, and intolerance towards various religious disagreement. Whereas in the context of a pluralistic Indonesian nation, whether of race, ethnicity, culture, class, and religion, religious messages should be delivered by inclusive proselytizing. Anyone who would articulate religious discourses in the public sphere of Indonesia, should ideally be through inclusive proselytizing. In the context of inclusive proselytizing, Islamic values such as justice (al-'adl), human rights, freedom (Hurriyah), democracy (Shura), universal benevolence (Khoir), egalitarian (Musawah), tolerance (tasamuh), balance ( tawazun), social ethics (morals), universal humanity (an-nas), as well as peace and safety contained in the doctrine of principle Islam but those are inclusive. Inclusive priciples could embrace all people regardless of race, culture, race, class, and even religion. This article is going to discuss the significance of Nurcholish Madjid‟s inclusive proselytizing for pluralistic Indonesian society.